The Use of Percepio Tracealyzer for the Development of FreeRTOS-based Applications - Khomenko, M.; Velihorskyi, O. (My University, 2020)
This paper discusses some problems of development and testing of FreeRTOS-based application. The use of Tracealyzer software tool is proposed to make this process more convenient. The benefits of such usage have been shown on typical issues that can be met in development and debug phase.
Keywords: microcontroller; RTOS; debug; embedded system; tracealyzer